2005
DOI: 10.1038/sj.onc.1209059
|View full text |Cite
|
Sign up to set email alerts
|

Human T-cell leukemia virus type 1 Tax attenuates γ-irradiation-induced apoptosis through physical interaction with Chk2

Abstract: Checkpoint kinase 2 (Chk2) is known to mediate diverse cellular responses to genotoxic stress. The fundamental role of Chk2 is to regulate the network of genomesurveillance pathways that coordinate cell-cycle progression with DNA repair and cell survival or death. Defects in Chk2 contribute to the development of both hereditary and sporadic human cancers. We now present evidence that the human T-cell leukemia virus type-1 (HTLV-1) Tax protein directly interacts with Chk2 and the kinase activity of Chk2 is inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 57 publications
0
31
1
Order By: Relevance
“…Subsequently, Park et al (48) confirmed the binding of Tax to Chk2 and agreed with our suggestion that Tax impairs Chk2 function. However, these authors observed that Tax represses the kinase activity of Chk2, based on in vitro findings, as the model for impaired function (49). This result appears to conflict with our demonstration of Tax-mediated activation of endogenous Chk2 (26).…”
Section: Discussioncontrasting
confidence: 55%
“…Subsequently, Park et al (48) confirmed the binding of Tax to Chk2 and agreed with our suggestion that Tax impairs Chk2 function. However, these authors observed that Tax represses the kinase activity of Chk2, based on in vitro findings, as the model for impaired function (49). This result appears to conflict with our demonstration of Tax-mediated activation of endogenous Chk2 (26).…”
Section: Discussioncontrasting
confidence: 55%
“…Activation of ATM stimulates Chk2, which phosphorylates p53 on serine-20, disrupting its interaction with Mdm2 and stabilizing p53 protein in response to DNA damage (Shieh et al, 1997;Chehab et al, 2000b). HTLV-I Tax interacts with and inhibits functions of Chk1/Chk2 (Haoudi et al, 2003;Park et al, 2004Park et al, , 2006. It is well established that HTLV-I Tax oncoprotein inhibits the function of the tumor suppressor p53 protein, although the mechanism of p53 inactivation in HTLV-I biology is still debated (Grassmann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was prematurely lost in Taxexpressing cells. Interestingly, Tax has also been shown to bind Chk2 (23,41). Although the effect of Tax binding on Chk2 kinase activity remains controversial, it has been proposed that Tax might alter the phosphorylation status of Chk2 and prevent its egress from chromatin (22).…”
Section: Vol 82 2008mentioning
confidence: 99%